ACT now: a mixed-methods evaluation of a nurse-led tobacco treatment program in a safety-net hospital - Thye Peng Ngo; Sasha N. Skinner; Neal Benowitz; Marlene Martin; Maya Vijayaraghavan (Addiction Science & Clinical Practice, 2026)
Abstract Background Tobacco use remains prevalent among patients hospitalized in safety-net settings, where co-occurring psychosocial and structural needs complicate treatment and contribute to persistent health disparities. However, little is known about how nurse-led tobacco treatment programs within addiction consult services are implemented, prioritized, and sustained. This study estimated tobacco use prevalence and correlates and examined multilevel factors influencing the implementation and sustainability of a novel licensed vocational nurse-led inpatient tobacco treatment model designed for resource-constrained safety-net settings. Methods We used a convergent mixed-methods design, guided by PRISM and RE-AIM frameworks, integrating retrospective electronic health record data with qualitative interviews in an urban safety-net hospital. Quantitative analyses included adults with index hospitalizations ≥ 24 h between August 1, 2019, and December 31, 2023 ( n = 38,068). We obtained qualitative data using semi-structured interviews with hospitalized patients receiving Addiction Care Team services ( n = 20) and clinical staff and leadership ( n = 10) and analyzed them thematically. We integrated quantitative and qualitative data to confirm and expand on findings. Results Current tobacco use was identified in 7,950 individuals (20.9%) and declined from 25.0% in 2019 to 18.3% in 2023. Tobacco use was associated with non-tobacco substance use disorder (aOR = 3.26, 95% CI = 3.06–3.48), discharge from psychiatric versus obstetric/gynecologic services (aOR = 2.94, 95% CI = 2.47–3.49), homelessness (aOR = 1.56, 95% CI = 1.45–1.67), and self-directed discharge (aOR = 1.37, 95% CI = 1.22–1.54). Qualitative findings explained these patterns, highlighting how competing priorities, workflow constraints, and structural barriers shape tobacco treatment delivery. Key implementation gaps included inconsistent screening, limited access to psychiatric units, and insufficient post-discharge follow-up. Conclusions Tobacco use among hospitalized patients in safety-net settings is closely linked with social and clinical vulnerability. Embedding a licensed vocational nurse-led tobacco treatment model within addiction consult services offers a scalable approach that extends tobacco care delivery to nurses while addressing co-occurring conditions, including substance use disorders, psychiatric comorbidity, homelessness, and self-directed discharge. However, effective and sustainable implementation will require consistent screening, equitable access across hospital units, and continuity of care after discharge. These findings identify actionable system-level targets and advance equity-focused tobacco treatment delivery in safety-net hospital systems.